Safety of Hydroxychloroquine, Favipiravir, and the Combination of Lopinavir and Ritonavir in the Treatment of the “First Wave” of the New Coronavirus Infection COVID-19 - B. K. Romanov (Регуляторные исследования и экспертиза лекарственных средств, 2020)
The review compares individual case safety reports (ICSRs) for hydroxychloroquine, favipiravir, and the lopinavir/ ritonavir combination registered in the VigiBase global database during 6 months in 2019 and the same period in 2020 which coincides with the global “first wave”. The aim of the study was to identify specific aspects of using these drugs for the treatment of COVID-19. There was an increase in the use of hydroxychloroquine, favipiravir, and the lopinavir/ritonavir combination during the pandemic, which was accompanied by a significant deterioration in the quantitative and qualitative safety profiles of these drugs. The review summarises the main risks of using these drugs for COVID-19 treatment and highlights the need for revision of the recommendations for their use in the context of the new coronavirus disease.